Radiation tolerance investigation of a Si detectors and microelectronics using NSC KIPT linacs - Dovbnya, A.N.; Maslov, N.I.; Dovbnya, N.A. (Вопросы атомной науки и техники, 2001)
A possibility of full irradiation tests of semiconductor detectors and microelectronics using electron accelerators are considered in the present work. The techniques for irradiation and for detector tests were described. The data on the efficiency of electron and bremsstrahlung action on the Si bulk material are presented.